ADVANCES IN PRESERVATION OF FRUITS AND VEGETABLES WITH BIOACTIVE COATINGS - ROJAS, ROMEO; VICENTE, ANTONIO A.; AGUILAR, CRISTÓBAL N. (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2015)
Bioactive compounds are a large group of compounds (antimicrobials, antioxidants, nutrients, etc.), but its use in edible films and coatings for application on fruits and vegetables has been very important because nowadays the consumers demand fruits and vegetables that are fresh, healthy, high quality and easy to prepare. A number of investigations have shown that the use of additives in edible films and coatings improve its functionability and provide compounds for human health. However, it is necessary to continue research that can generate specific or tailor-made edible films and coatings for each product with the best characteristics for preservation. In this review we present and analyze the concepts, progress and perspectives in the design and application of edible films and coatings for fruits and vegetables in order to define the challenges and opportunities that this topic of study in the field of science, technology and food engineering.